Can match play kicking and physical performance outcomes be replicated in an Australian football small-sided game?. Issue 4 (1st October 2020) - Bonney, Nathan; Berry, Jason; Ball, Kevin; Larkin, Paul
ABSTRACT: Introduction: This study investigated if the technical and physical match performance outcomes can be replicated in a 5v6 small-sided game (SSG). Methods: Sixteen youth Australian Football (AF) players (mean ± SD; age 16.5 ± 1.0 years, height 179.1 ± 8.0 cm, weight 69.5 ± 9.5 kg) were randomly recruited. Participants were assessed in the SSG during the week prior to the assessed match play. The technical variables assessed were kicking proficiency, number of kicks executed and the amount of time each player had with the ball before kick execution (i.e., under 2s, 2-4s, over 4s). The physical variables assessed were odometer, meters travelled per minute, maximum velocity and percentage of high intensity running. Results: The results suggest kicking proficiency, the number of kicks executed, meters travelled per minute and percentage of high intensity running were all higher in the SSG than during match play. Furthermore, the SSG had less technical variability in comparison to match play. During match play, players had less time affordance to execute a kick and achieved higher maximum running velocities than during the SSG. Conclusion: This research provides coaches with greater insights into the technical and physical performance demands of match play.